A Randomized Trial Comparing Classical Participatory Design to VandAID, an Interactive CrowdSourcing Platform to Facilitate User-centered Design - Dufendach, Kevin R.; Koch, Sabine; Unertl, Kim M.; Lehmann, Christoph U. (Methods of Information in Medicine, 2017)
Background: Early involvement of stakeholders in the design of medical software is particularly important due to the need to incorporate complex knowledge and actions associated with clinical work. Standard user-centered design methods include focus groups and participatory design sessions with individual stakeholders, which generally limit user involvement to a small number of individuals due to the significant time investments from designers and end users.Objectives: The goal of this project was to reduce the effort for end users to participate in co-design of a software user interface by developing an interactive web-based crowd- sourcing platform.Methods: In a randomized trial, we compared a new web-based crowdsourcing platform to standard participatory design sessions. We developed an interactive, modular platform that allows responsive remote customization and design feedback on a visual user interface based on user preferences. The responsive canvas is a dynamic HTML template that responds in real time to user preference selections. Upon completion, the design team can view the user’s interface creations through an administrator portal and download the structured selections through a REDCap interface.Results: We have created a software platform that allows users to customize a user interface and see the results of that customization in real time, receiving immediate feedback on the impact of their design choices. Neonatal clinicians used the new platform to successfully design and customize a neonatal handoff tool. They received no specific instruction and yet were able to use the software easily and reported high usability.Conclusions: VandAID, a new web-based crowdsourcing platform, can involve multiple users in user-centered design simultaneously and provides means of obtaining design feedback remotely. The software can provide design feedback at any stage in the design process, but it will be of greatest utility for specifying user requirements and evaluating iterative designs with multiple options.
Keywords: Computers; informatics; human factors and engineering; human-computer interface